Trade Mark Protection for Smells, Tastes and Feels – Critical Analysis of Three Non-Visual Signs in the EU - Simon Geiregat (IIC - International Review of Intellectual Property and Competition Law, 2022)
This article focuses on the ability to protect three non-traditional signs as trade marks in the EU: smell (olfactory marks), taste (gustatory marks) and feel (tactile marks). All three types of subject matter can meet the definition of a sign. According to the majority view in literature and practice, none of the three can currently be represented on the register with sufficient clarity and precision, however. It is argued that the veracity of that finding essentially boils down to a lack of vocabulary and IT solutions, and that it depends on the level of detail that can be expected from non-visual signs. Theoretically, distinctiveness is less of an obstacle to protection. Although some signs need to acquire distinctiveness through use, distinctiveness should be assessed on a case-by-case basis and it cannot be excluded that there are smells, tastes and feels that are inherently distinct. In practice, authorities seem to uphold excessive thresholds for olfactory, gustatory, and especially tactile marks. This is understandable in the light of their potential scope, which lies at the heart of the debate on their eligibility for protection. Indeed, granting protection to these three types of signs carries the risk of depleting and propertising almost anything. Although this might be true, it is contended that more research is needed and that there is no legislative basis for a Freihaltebedürfnis (need to keep signs freely available) in this respect. After considering fundamental rights and public policy as alternative means of channelling that concern, the article concludes that it is for the EU legislator to evaluate whether to exclude certain signs from trade mark law.
Keywords: 340; Trade marks; Non-traditional; Olfactory; Gustatory; Tactile; Haptic